Statistics:A guide to the unknown /Edited by Judith M. Tanur [and others] - Tanur, Judith M., |e ed.
Papers contributed at the invitation of the Joint Committee on the Curriculum in Statistics and Probability of the American Statistical Association and the National Council of Teachers of Mathematics